Penerapan Model Pembelajaran Teams Games Tournament Berbasis Ranking One Civic Education Untuk Meningkatkan Hasil Belajar Siswa - Laili, Innayatul; Dayati, Umi; Rochmadi, Nur Wahyu (Universitas Negeri Malang, 2021)
The purpose of this study was to explain the feasibility of learning using the team games tournament-based Ranking One Civic Education (ROCE) model in teaching and learning activities on Pancasila and Civic Education (PPKn) subjects and to analyze the improvement of student learning outcomes after the ROCE Game-based learning method was applied to PPKn subjects. This study used a classroom action research approach with qualitative and quantitative data as material for analysis. This study used two cycles with two meetings for each cycle. As for the process of implementing the ROCE Game, it was found that 13-14 indicators were carried out well in cycle I, while in the learning process in cycle II, an average of 15 indicators were obtained from a total of 17 indicators of learning implementation by teachers. In the first cycle, an average of 11 indicators was obtained and in the second cycle, an average of 12-13 indicators was obtained from a total of 14 indicators of learning implementation by students. The increase in learning outcomes taken based on the post-test score in cycle I was 77.7 percent, then an increase in the post-test score in cycle II became 86.1 percent. So, tournament-based teams games learning model Ranking One Civic Education could increase student learning outcomes.